Agmatine attenuates stress- and lipopolysaccharide-induced fever in rats - ARICIOĞLU, FEYZA (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Physiological stress evokes a number of responses, including a rise in body temperature, which has been suggested to be the result of an elevation in the thermoregulatory set point. This response seems to share similar mechanisms with infectious fever. The aim of the present study was to investigate the effect of agmatine on different models of stressors [(restraint and lipopolysaccaride (LPS)] on body temperature. Rats were either restrained for 4 h or injected with LPS, both of these stressors caused an increase in body temperature. While agmatine itself had no effect on body temperature, treatment with agmatine (20, 40, 80 mg/kg intraperitoneally) dose dependently inhibited stress- and LPS-induced hyperthermia. When agmatine (80 mg/kg) was administered 30 min later than LPS (500 mu g/kg) it also inhibited LPS-induced hyperthermia although the effect became significant only at later time points and lower maximal response compared to simultaneous administration. To determine if the decrease in body temperature is associated with an anti-inflammatory effect of agmatine, the nitrite/nitrate levels in plasma was measured. Agmatine treatment inhibited LPS-induced production of nitrates dose dependently. As an endogenous molecule, agmatine has the capacity to inhibit stress- and LPS-induced increases in body temperature. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: agmatine; restraint stress; lipopolysaccharide; nitric oxide; arginine; nitrites; NITRIC-OXIDE PRODUCTION; ARGININE; PROLIFERATION; INFLAMMATION; IMIDAZOLINE; MACROPHAGES; MODULATION; INDUCTION; PATHWAYS; BRAIN